The Trust of UIN Sunan Ampel Surabaya Students in Mainstream and Social Media Usage - Fikry Zahria Emeraldien; Choe Rotuzzakia; Rada Awaliyah; Alfi Faridah; Huey-Rong Chen (Lingkar Studi Komunikasi (LISKI), 2023)
This research studies the trust of Generation Z in journalistic media -or commonly known as mainstream media- and social media in order to get information. It also studies the factors that make the media trustworthy. This study uses a quantitative approach to the survey method. The questionnaire instrument was written via the Google Form platform while the secondary data for this research came from literature and previous research. The data collection technique for this research was non-probability sampling through 180 students born in 1997-2004 at Universitas Islam Negeri Sunan Ampel Surabaya. The process of distributing the questionnaire was carried out during April 2022. This research shows that generation Z access journalistic media and social media in getting news or information. The results of the study show that the most trusted mainstream media is online journalistic media chosen by 46.1% of respondents. Meanwhile, the most trusted social media by respondents is Twittet with a survey result of 39.2%. Journalistic media is trusted because of the data and facts presented, while social media is trusted because it can balance official information from certain agencies. Keywords: Journalistic,Social Media, Media Trust, Mainstream Media, Generation Z